CT Muscle Density, D3Cr Muscle Mass, and Body Fat Associations With Physical Performance, Mobility Outcomes, and Mortality Risk in Older Men. Issue 4 (16th September 2021) - Orwoll, Eric S; Blackwell, Terri; Cummings, Steven R; Cauley, Jane A; Lane, Nancy E; Hoffman, Andrew R; Burghardt, Andrew J; Evans, William J; Cawthon, Peggy M
Abstract: Background: Muscle mass declines with age, while body adiposity increases. Sarcopenic obesity has been proposed to be particularly deleterious. However, previous methods for estimating muscle mass have been inadequate, and the relative contributions of total body fat versus muscle fat to adverse outcomes have been unclear. Method: In a large cohort of older men ( N = 1 017), we measured muscle mass (D3 -creatine dilution), muscle density (high-resolution peripheral quantitative computed tomography in the diaphyseal tibia) as a proxy of muscle fat, and total body fat (dual-energy x-ray absorptiometry). We examined their associations with physical performance (walking speed, grip strength, chair stand time), the risk of mobility outcomes (mobility limitations, mobility disability), and the risk of death over ~5 years. Results: In combined models, lower muscle mass and muscle density were independently associated with worse physical performance and the risk of adverse outcomes, while total body fat was minimally related to physical performance and not related to mobility outcomes or mortality. For example, the relative risks for mortality per 1 standardized unit increase in muscle density, muscle mass, and total body fat were 0.84 (95% confidence interval: 0.74, 0.96), 0.70 (0.57, 0.86), and 0.90 (0.64, 1.25), respectively. Conclusions: Muscle mass and muscle density were associated with physical performance and adverse outcomes, and had independent, additive effects. There was little additional contribution of total body fat.